Passage of an Anterior Odontoid Screw through Gastrointestinal Tract - L. Leitner; C. I. Brückmann; M. M. Gilg; G. Bratschitsch; P. Sadoghi; A. Leithner; R. Radl (Case Reports in Medicine)
Purpose. Anterior screw fixation has become a popular surgical treatment method for instable odontoid fractures. Screw loosening and migration are a rare, severe complication following anterior odontoid fixation, which can lead to esophagus perforation and requires revision operation. Methods. We report a case of screw loosening and migration after anterior odontoid fixation, which perforated the esophagus and was excreted without complications in a 78-year-old male patient. Results. A ventral dislocated anterior screw perforated through the esophagus after eight years after implantation and was excreted through the gastrointestinal (GI) tract. At a 6-month follow-up after the event the patient was asymptomatic. Conclusion. Extrusion via the GI tract is not safe enough to be considered as a treatment option for loosened screws. Some improvements could be implemented to prevent such an incident. Furthermore, this case is a fine example that recent preoperative imaging is mandatory before revision surgery for screw loosening.